2020
DOI: 10.3389/fneur.2020.600917
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Patient Selection for Interhospital Transfer and Endovascular Therapy in Acute Ischemic Stroke: Real-World Data From a Supraregional, Hub-and-Spoke Neurovascular Network in Germany

Abstract: Background: Interhospital transfer for endovascular treatment (EVT) within neurovascular networks might result in transfer of patients who will not undergo EVT (futile transfer). Limited evidence exists on factors associated with the primary patient selection for interhospital transfer from primary stroke centers (PSCs) to comprehensive stroke centers (CSCs), or EVT-workflow parameters that may render a transfer futile.Methods: A prospective, registry-based study was performed between July 1, 2017 and June 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
3
3
1
Order By: Relevance
“…Our findings support a recent study showing that MT is an effective treatment in the extended time frame [5] and NCCT can be safely used to select appropriate patients [11]. Furthermore, they support recent studies showing that hub-and-spoke stroke network infrastructures enable access to successful MT in patients with stroke living remotely [12,13]. In keeping with other hub-and-spoke stroke transfer studies, we found NIHSS score, ASPECTS and age to be important determinants of outcome [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support a recent study showing that MT is an effective treatment in the extended time frame [5] and NCCT can be safely used to select appropriate patients [11]. Furthermore, they support recent studies showing that hub-and-spoke stroke network infrastructures enable access to successful MT in patients with stroke living remotely [12,13]. In keeping with other hub-and-spoke stroke transfer studies, we found NIHSS score, ASPECTS and age to be important determinants of outcome [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…These processes can be further optimized if the primary stroke centers and comprehensive stroke centers are integrated in a network and use tools such as teleconsulting and teleradiology. 28 Our results support a recent expert statement, recommending repeated imaging in transfer patients only in cases of clinical deterioration or improvement, 29 as this can significantly reduce door-to-treatment times in these patients.…”
Section: Discussionsupporting
confidence: 87%
“…We defined high PSC volume as >12 EVT referrals per year based on the distribution of our data; only 15% of PSCs had >12 annual EVT referrals. Although few previous studies have reported on EVT referral volumes, average PSC volumes in our study seem relatively high compared to those found in regions in Germany and Australia (six annual EVT referrals per PSC in our study vs. four in both Germany and Australia) [ 26 , 27 . Nonetheless, it is possible that for even higher EVT referral volumes, an association with shorter time to treatment would exist.…”
Section: Discussioncontrasting
confidence: 75%